Chiroptical detection of a model ruthenium dye in water by circularly polarized-electrochemiluminescence. Issue 44 (29th April 2020) - Voci, Silvia; Zinna, Francesco; Arrico, Lorenzo; Grass, Stéphane; Bouffier, Laurent; Lacour, Jérôme; Di Bari, Lorenzo; Sojic, Neso
Abstract : We demonstrate the possibility to detect selectively the two single enantiomers of a model [Ru(bpy)3 ] 2+ -based dye by circularly polarized-electrochemiluminescence (CP-ECL). Abstract : We demonstrate the possibility to detect selectively the two single enantiomers of a model [Ru(bpy)3 ] 2+ -based dye by circularly polarized-electrochemiluminescence (CP-ECL). This new aspect of the ECL emission combines the chiral information intrinsic to CPL methods with an electrogeneration of the excited state. Thus, it opens the possibility to perform ECL-based bioassays or microscopy with efficient chiral dyes.